2018
DOI: 10.1002/hed.25114
|View full text |Cite
|
Sign up to set email alerts
|

Major prognostic factors for recurrence and survival independent of the American Joint Committee on Cancer eighth edition staging system in patients with cutaneous squamous cell carcinoma treated with multimodality therapy

Abstract: In-transit metastasis was significantly associated with locoregional recurrence, OS, and cause-specific mortality. Efforts should be made to define in-transit metastasis in the staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…It remains to be seen whether this staging system or additional variables, such as immunosuppression, in-transit metastasis, or genetic profiles, may improve prognostic stratification in patients with these tumors. 18…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen whether this staging system or additional variables, such as immunosuppression, in-transit metastasis, or genetic profiles, may improve prognostic stratification in patients with these tumors. 18…”
Section: Discussionmentioning
confidence: 99%
“…Risk increased with age, in males, in patients with immunosuppression, in higher deprivation quintiles, and location on the ear and lip [25]. Immunosuppression in patients with cSCC may include human immunodeficiency virus (HIV) infection, solid organ transplant, hӕmatopoietic stem cell transplant, or chronic lymphocytic leukemia (CLL) [38]. Several studies have shown worse outcomes for cSCC in immunosuppressed patients compared to immunocompetent patients [39,40].…”
Section: Prognosismentioning
confidence: 99%
“…Our definitive surgical cohort showed an estimated 2-and 5-year DFS of 64% and 49%, respectively, despite 80% of patients receiving adjuvant treatment. Single-institution reviews have reported 5-year DFS and locoregional control rates from 59% to 78% 6,11,12,17,18,20 ; in a recent review of 101 patients receiving surgery and adjuvant RT for Bold type denotes statistical significance at p < .05. CI = confidence interval; ENE = extranodal extension; HR = hazard ratio; LVSI = lymphovascular space invasion; PD = poorly differentiated; PNI = perineural invasion; RT = radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Those are based mostly on single-institution reviews, as there are no national cancer registries that currently track the outcomes of cSCC. Risk factors for HNcSCC reportedly associated with worse outcomes include: advanced age, 6,7 size/diameter, 4,5,8,9 depth of invasion, 4,5,9 perineural invasion (PNI), 4,5,10,11 location, 5 poorly differentiated histology, 4,5,9,12,13 recurrent disease, 4 extranodal extension (ENE) of lymph nodes, 7,8,14,15 lymph node ratio, 6,16,17 immunosuppression, 6,11,[14][15][16][18][19][20] positive margins, 13,15,19,21 parotid metastases, 19,22 and disease-free interval. 23 Although many of these have been taken into consideration in the American Joint Committee on Cancer (AJCC) 8th Edition staging of HNcSCC, several others have been omitted.…”
Section: Introductionmentioning
confidence: 99%